TARGET COMPLIANCE PELAKU USAHA MAKANAN DAN MINUMAN PENGGUNAAN PLASTIK SEKALI PAKAI DI KOTA SEMARANG - Budi Sulistyaningrum, An Nisaa’; Sunu Astuti, Retno; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
Plastic waste has become a problem at the local and international levels. Both directly and indirectly, plastic waste affects ecosystems in the sea, land, and even freshwater sustainability globally. As the amount of plastic waste increases, more and more governments from various regions are banning or imposing levies on single-use plastics. Semarang City through Semarang Mayor Regulation No. 27/2019 has regulated the use of single-use plastics, which aims to control the generation of single-use plastic waste. The public is asked to switch to using environmentally friendly substitute products, including food and beverage businesses. This study aims to analyze the target compliance and factors inhibiting the target compliance of single-use plastic policy in Semarang City. This study aims to analyze the target compliance and factors inhibiting the target compliance of single-use plastic policy in Semarang City. The method in this study uses a mixed method with primary data derived from questionnaires, interviews, and observations. Supported by secondary data from news, social media, and various literatures. The results showed that the target compliance of food and beverage business actors is at a low level, which is equivalent to 46,3%. Meanwhile, based on the target compliance factor, it is found that the compliance of food and beverage business actors is still not optimal due to inhibiting factors, including the lack of information received by the target group, there are no incentives and sanctions, and weak supervision by the government.